2020
DOI: 10.2478/sjdv-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IHC Ki-67 with Clinical Correlation in Psoriasis

Abstract: Introduction. Psoriasis is a chronic inflammatory skin disease with hyperproliferation, abnormal differentiation and inflammatory infiltration in epidermis and dermis. Sometimes it is clinically and histopathologically challenging to distinguish psoriasis from other non-psoriatic psoriasiform dermatoses (NPPD) like eczema, pityriasis rosea, pityriasis rubra pilaris, and lichen simplex chronicus. Ki-67 is a non-histone nuclear protein complex that regulates the cell cycle and is the most widely used proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The ki‐67 stain was found in the whole epidermis in both groups before treatment. Two studies reported by Engin Sezer et al, 2015 26 and Borade et al, 2020 27 stated that the over‐expression of Ki‐67 in psoriatic lesions suggests an abnormality of cell cycle regulation related to the hyper‐proliferation and abnormal differentiation of psoriatic keratinocytes, implying that it may be involved in the pathogenesis of psoriasis. After 12 weeks of treatment, 70% of group A lesions showed Ki‐67 stain in the basal layer only in comparison with 20% in group B.…”
Section: Discussionmentioning
confidence: 99%
“…The ki‐67 stain was found in the whole epidermis in both groups before treatment. Two studies reported by Engin Sezer et al, 2015 26 and Borade et al, 2020 27 stated that the over‐expression of Ki‐67 in psoriatic lesions suggests an abnormality of cell cycle regulation related to the hyper‐proliferation and abnormal differentiation of psoriatic keratinocytes, implying that it may be involved in the pathogenesis of psoriasis. After 12 weeks of treatment, 70% of group A lesions showed Ki‐67 stain in the basal layer only in comparison with 20% in group B.…”
Section: Discussionmentioning
confidence: 99%